Pharmaceutical concentration using organic solvent forward osmosis for solvent recovery - Cui, Yue; Chung, Tai-Shung (Nature communications, 2018)
The organic solvent forward osmosis (OSFO) process can simultaneously concentrate the active pharmaceutical ingredients (APIs) and recover the organic solvents. Here we demonstrate and evaluate an OSFO process for solvent recovery. In this demonstration, OSFO was conducted in different solvents with different draw solutes. The OSFO process shows rejections >98% when recovering organic solvents from different feed solutions, even when the feed concentration is as high as 20 wt%. More importantly, all systems exhibit relatively low ratios of reverse solute flux to solvent flux, indicating that the adverse effects of using hazardous draw solutions could be minimized. Nevertheless, the use of non-hazardous draw solutes such as citric acid is highly recommended to remove any potential risk, and it has been demonstrated. Herein, the OSFO process is a promising technology for solvent recovery as it possesses a reasonable solvent flux, low reverse solute flux and requires no external pressure. Solvent recovery is an important process in the pharmaceutical industry, but organic solvent nanofiltration membranes operate under high pressures. Here the authors demonstrate organic solvent forward osmosis — an alternative process that does not require application of external pressure and may prove to be economically favorable.